Respuesta :

Answer:

Step-by-step explanation:

3. 10x + 6 = 8x

   8x = 10x + 6

   -2x = 6

  x = -3

4. y = 8(1) - 5= 8 - 5 = 3

   y = 8(2) - 5 = 16 - 5 = 11

    y = 8(5) - 5 = 40 - 5 = 35

    y = 8(0) - 5 = 0 - 5 = -5

    y = 8(-1) - 5 = -8 - 5 = -13

Number 3 :

[tex]10x + 6 = 8x[/tex]

[tex]6 = 8x - 10x[/tex]

[tex]6 = - 2x[/tex]

[tex]6 \div - 2 = x[/tex]

[tex] - 3 = x[/tex]

Number 4 :

[tex]y = 8x - 5[/tex]

When [tex] x = 1, y = \bold{ 3} [/tex]

[tex]y = (8 \times 1)- 5[/tex]

[tex]y = 8 - 5[/tex]

[tex]y = 3[/tex]

When [tex] x = 2, y = \bold{ 11} [/tex]

[tex]y = (8 \times 2)- 5[/tex]

[tex]y = 16 - 5[/tex]

[tex]y = 11[/tex]

When [tex] x = 5, y = \bold{35} [/tex]

[tex]y = (8 \times 5)- 5[/tex]

[tex]y = 40 - 5[/tex]

[tex]y = 35[/tex]

When [tex] x = 0, y = \bold{-5} [/tex]

[tex]y = (8 \times 0)- 5[/tex]

[tex]y = 0 - 5[/tex]

[tex]y = - 5[/tex]

When [tex] x = -1, y = \bold{-13} [/tex]

[tex]y = (8 \times - 1)- 5[/tex]

[tex]y = - 8 - 5[/tex]

[tex]y = - 13[/tex]